Hubungan Pembelajaran Hybrid (Online-Offline) dengan Nilai Akademik, Kompetensi Keterampilan dan Kepuasan Mahasiswa pada Mata Kuliah Asuhan Persalinan dan Bayi Baru Lahir - Yeti Yuwansyah; Herry Herman; Ike R. Husen (Faletehan Health Journal, 2024)
The combination of online and offline learning had an impact on students' affective knowledge and skills. This study investigated the relationship between combined offline-online learning method and students’ competency, academic grades, and satisfaction in the Childbirth and Newborn Care Course. This study employed a retrospective cohort design and involved 175 students who completed the Childbirth and Newborn Care Course (attending more than 14 sessions) and the final exam. The data collection utilized the lecturer’s grade records and for the evaluation of students’ satisfaction evaluations the existing academic system was used. Chi-square analysis revealed a significant relationship between the combined offline-online method and students’ skill competency (r = 0.000) and academic grades in the Childbirth and Newborn Care Course. However, no significant relationship was observed between the combined offline and online method and student satisfaction. These findings suggested a need for developing teaching method from conventional to combined offline and online learning. The combined offline-online learning must be well-designed and aligned with learning objectives so that students can be engaged in the learning process properly.